Determining Order Size on Joint Inventory of Single Buyer and Seller With Fuzzy Demand - Nasa Fadiyah; Said Salim Dahda (Universitas Islam Raden Rahmat, Malang, 2025)
Every company generally has problems about the company's inventory control system. The ability to meet demand with the right amount, time and location. Common models such as EOQ / EPQ are often used in inventory planning and control. The assumption of using this model requires cost and demand data that must be known and fixed. So that in solving inventory system problems sometimes there is a lack of information about similar data. So the development is needed to adjust to the conditions and industrial environment. One is an integration model between suppliers and buyers that results in lot sizes that minimize total inventory costs. Then it can be done an integration between suppliers and buyers by using fuzzy. This Model is designed to overcome the uncertainty of demand by describing it in the form of triangular fuzzy numbers. The results of the research using this method and involving an iterative approach obtained optimal results where the production quantity was 57,07 units and the delivery frequency was 3 times so that it could minimize the total inventory cost with a total cost of 242,05.